Evaluation of power storage circuit for piezoelectric energy harvester in impact mode - Basari, Amat Amir; Hashimoto, Seiji (Semarak Ilmu, 2024)
Power storage circuit is crucial to the performance of the vibration energy harvesting system as it will affect the amount of energy that can be harvested. The objective of this paper is to discuss the design and evaluation of power storage circuit for the vibration-based impact mode piezoelectric energy harvester. The proposed power storage circuit consists of rectifier circuit with rectifier capacitor, voltage regulator and the storage device. Evaluation on the rectifier circuit and the power storage circuit is carried out with variation in the resistive load and some other components. Results show that for the multiple impact input, full wave rectifier produces higher output than that of the other circuit. In addition to that, the proposed storage circuit can produce a stable output voltage and output power at about 40 Hz of operating frequency range. This show that piezoelectric energy harvester in impact mode can operate well with the proposed power storage circuit.